Radiomics of magnetic resonance imaging for assessment of pathological complete response to neoadjuvant therapy and long-term survival in breast cancer - N. V. Petrova; G. G. Karmazanovsky; E. V. Kondratyev; A. Yu. Popov; M. V. Rostovtsev; N. Yu. Germanovich; D. V. Kalinin (Исследования и практика в медицине, 2023)
Breast cancer (BC) is the most common malignant disease. The use of neoadjuvant drug therapy increases the likelihood of achieving a complete pathomorphological response (pCR), leads to an increase in resectability and ablation; helps to determine the sensitivity of tumor cells to chemopreventive agents, thereby improving the patient’s prognosis. Since pathomorphological assessment occurs aﬅer surgery, it is necessary to develop methods for non-invasive response assessment for timely correction of the volume of treatment. One such method is magnetic resonance imaging (MRI). Assessment of the obtained images using texture analysis allows to increase the accuracy of the method both in the control of neoadjuvant treatment and in the assessment of the response to neoadjuvant therapy during preoperative planning.This article provides an analysis of the literature data on the potential to improve the prognostic value of breast MRI in assessing the complete pathomorphological response to neoadjuvant drug treatment of breast cancer using texture analysis of data.